CREATING CONDITIONS FOR ENTREPRENEURSHIP DEVELOPMENT BY LOCAL SELF-GOVERNMENTS - Kacprzak, Marzena (Acta Scientiarum Polonorum. Oeconomia, 2009)
The paper concentrates on policy instruments of the local development. Self-government should take different actions which aim at encouraging entrepreneurs for cooperation, creating conditions for setting up enterprises and their development, initiating economic undertakings for development harmonization. Self-government authorities could take the actions in the sphere of property, labour and natural resources management. Creation of local entrepreneurship development conditions is connected with legal conditioning, financial competences as well as economic and infrastructural incentives for business entities.